2019
DOI: 10.4314/jasem.v23i5.26
|View full text |Cite
|
Sign up to set email alerts
|

Soil physicochemical properties as influenced by persistent herbicide weed control in some communities in Ondo State, Nigeria

Abstract: This study identified areas where different types of herbicide were used for municipal weed control in selected residential communities in Akure, Akungba-Akoko and Owo in Ondo State, Nigeria. A survey of the communities was carried out to identify sites maintained with herbicides (test sites) and those without herbicide history (control sites). Composite soil samples collected from each site were analyzed using standard laboratory procedures for the determination of selected soil physical and chemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Similar report by Ref. [ 36 ] revealed that some communities in Ondo State, Nigeria that have been exposed to herbicides had soil pH ranges from slightly acidic to neutral. So, at this pH level, less pesticide will be absorbed at the soil's surface.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar report by Ref. [ 36 ] revealed that some communities in Ondo State, Nigeria that have been exposed to herbicides had soil pH ranges from slightly acidic to neutral. So, at this pH level, less pesticide will be absorbed at the soil's surface.…”
Section: Resultssupporting
confidence: 79%
“…The soil detected inside the examined sites belonged to the textural class of sandy-loamy. The soils' high concentration of sand may be a result of Nigeria's typically sandy, humid tropical soils [ 42 ].The sandy nature of the soil encourages the leaching of numerous soil properties into the groundwater, rivers, lakes, and streams nearby during the rainy season when herbicide treatment occurs [ 36 ]. Soils that have a significant amount of sand particles are referred to as Sand, loamy sand, or sandy loam soils and are considered to be coarse in texture.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the use of the herbicides has effectively aid in controlling and checking the growth of weeds, which are the major competitors to crops for soil nutrients and water. However, some of these herbicides were reported to have significant effect on both physicochemical and microbial components of soil [4,5]. A significant effect of herbicides like glyphosate, triclopyr and fluroxypyr on soil physicochemical properties that include pH and soil nitrogen was reported by [6].…”
Section: Introductionmentioning
confidence: 99%